Modulation of immune cell function, IDO expression and kynurenine production by the quorum sensor 2-heptyl-3-hydroxy-4-quinolone (PQS) - Ogbechi, Joy; Huang, Yi-Shu; Clanchy, Felix I. L.; Pantazi, Eirini; Topping, Louise M.; Darlington, L. Gail; Williams, Richard O.; Stone, Trevor W. (Frontiers in Immunology, 2022)
Many invasive micro-organisms produce ‘quorum sensor’ molecules which regulate colony expansion and may modulate host immune responses. We have examined the ability of Pseudomonas Quorum Sensor (PQS) to influence cytokine expression under conditions of inflammatory stress. The administration of PQS in vivo to mice with collagen-induced arthritis (CIA) increased the severity of disease. Blood and inflamed paws from treated mice had fewer regulatory T cells (Tregs) but normal numbers of Th17 cells. However, PQS (1μM) treatment of antigen-stimulated lymph node cells from collagen-immunised mice in vitro inhibited the differentiation of CD4+IFNγ+ cells, with less effect on CD4+IL-17+ cells and no change in CD4+FoxP3+Tregs. PQS also inhibited T cell activation by anti-CD3/anti-CD28 antibodies. PQS reduced murine macrophage polarisation and inhibited expression of IL1B and IL6 genes in murine macrophages and human THP-1 cells. In human monocyte-derived macrophages, IDO1 gene, protein and enzyme activity were all inhibited by exposure to PQS. TNF gene expression was inhibited in THP-1 cells but not murine macrophages, while LPS-induced TNF protein release was increased by high PQS concentrations. PQS is known to have iron scavenging activity and its suppression of cytokine release was abrogated by iron supplementation. Unexpectedly, PQS decreased the expression of indoleamine-2, 3-dioxygenase genes (IDO1 and IDO2), IDO1 protein expression and enzyme activity in mouse and human macrophages. This is consistent with evidence that IDO1 inhibition or deletion exacerbates arthritis, while kynurenine reduces its severity. It is suggested that the inhibition of IDO1 and cytokine expression may contribute to the quorum sensor and invasive actions of PQS.